A spatiotemporal atlas of organogenesis in the development of orchid flowers. Issue 17 (12th September 2022) - Liu, Chang; Leng, Jing; Li, Yonglong; Ge, Tingting; Li, Jinglong; Chen, Yamao; Guo, Chunce; Qi, Ji
Abstract: Development of floral organs exhibits complex molecular mechanisms involving the co-regulation of many genes specialized and precisely functioning in various tissues and developing stages. Advance in spatial transcriptome technologies allows for quantitative measurement of spatially localized gene abundance making it possible to bridge complex scenario of flower organogenesis with genome-wide molecular phenotypes. Here, we apply the 10× Visium technology in the study of the formation of floral organs through development in an orchid plant, Phalaenopsis Big Chili. Cell-types of early floral development including inflorescence meristems, primordia of floral organs and identity determined tissues, are recognized based on spatial expression distribution of thousands of genes in high resolution. In addition, meristematic cells on the basal position of floral organs are found to continuously function in multiple developmental stages after organ initiation. Particularly, the development of anther, which primordium starts from a single spot to multiple differentiated cell-types in later stages including pollinium and other vegetative tissues, is revealed by well-known MADS-box genes and many other downstream regulators. The spatial transcriptome analyses provide comprehensive information of gene activity for understanding the molecular architecture of flower organogenesis and for future genomic and genetic studies of specific cell-types.